An infected urachal cyst is a rare differential diagnosis for an acute abdomen in adult female: a case report - Bettaiah, Ramesh; Kurkuri, Shraddha Neminath; Chandramouli, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
An infected urachal cyst is one of a spectrum of presentations of urachal pathology, all of which are rare in adulthood. Patients tend to present in a heterogeneous fashion, making diagnosis difficult. A 45-year old lady presented with sudden onset of lower abdominal pain and fever since 10 days. There was tenderness and focal rigidity in the right iliac fossa. Abdominal ultrasonography revealed suprapubic collection with mixed echogenecity. On diagnostic laparoscopy; urachal abscess was confirmed and excised. Urachal disease is usually detected in infancy and childhood. Infection is the usual mode of presentation amongst adults otherwise the condition usually remains asymptomatic. Diagnosis is often made after exploratory laparotomy or laparoscopy. Ultimately, surgical intervention is the treatment of choice. Complete excision is important because malignant degeneration of the remnant is possible. In cases where a pre-operative diagnosis has been made, a staged approach with antibiotics followed by surgery has been recommended.